2012
DOI: 10.1111/jocs.12044
|View full text |Cite
|
Sign up to set email alerts
|

Left Main Coronary Atresia

Abstract: Left main coronary artery atresia (LMCAA) is one of the least frequently observed congenital coronary anomalies. We describe a case series of LMCAA, highlighting the clinical presentation, characteristic, and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…1,2 Congenital atresia of the LMCA is a very rare disease, and only a small number of reports have been published. 3 In the present case, the absence of aortitis, Kawasaki disease history, calcium deposits, arteriosclerosis, and of continuity between the LMCA and the proximal tip of the LAD suggested a congenital phenotype. Furthermore, on CTA the LAD was occluded, with no evidence of ostial stamp of the LAD distal tip, and the proximal tip of the LAD seemed to approach the main pulmonary artery while leaving a trabecular trace.…”
Section: Images In Cardiovascular Medicine Congenital Ostial Atresia supporting
confidence: 44%
“…1,2 Congenital atresia of the LMCA is a very rare disease, and only a small number of reports have been published. 3 In the present case, the absence of aortitis, Kawasaki disease history, calcium deposits, arteriosclerosis, and of continuity between the LMCA and the proximal tip of the LAD suggested a congenital phenotype. Furthermore, on CTA the LAD was occluded, with no evidence of ostial stamp of the LAD distal tip, and the proximal tip of the LAD seemed to approach the main pulmonary artery while leaving a trabecular trace.…”
Section: Images In Cardiovascular Medicine Congenital Ostial Atresia supporting
confidence: 44%
“…The left coronary circulation is supplied by the RCA through collaterals. In paediatric patients, LMCAA usually coexists with other cardiac abnormalities such as valvular disease with the onset of symptoms early in life 4. In adults, LMCAA can be found in isolation and is usually asymptomatic early in adult life 5.…”
Section: Discussionmentioning
confidence: 99%
“…The overall incidence is estimated between 0.6% and 1.3% [1][2][3]. A recent review found a total of only 53 cases of LMCA atresia ever reported in the literature, including both pediatric and adult cases [3]. The authors found more than half of the patients survived into adulthood with a presentation of either angina or atypical chest pain.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, left main coronary artery (LMCA) atresia remains one of the least frequently observed variations. The overall incidence is estimated between 0.6% and 1.3% [1][2][3]. A recent review found a total of only 53 cases of LMCA atresia ever reported in the literature, including both pediatric and adult cases [3].…”
Section: Introductionmentioning
confidence: 99%